IN-SHOP EMOTIONS DAN PERCEIVED VALUE: FAKTOR PENENTU DALAM MEMBENTUK REPURCHASE INTENTION - Mei Monika Putri; Amelindha Vania (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The rapid development of information technology in the business world has undergone major global transformations. This development has spurred the emergence of various types of modern retail businesses, including KTV, which have become popular in various countries and created increasingly competitive competition, which is in line with the Stimulus-Organism-Response (SOR) theory that explains how external stimuli affect individual organisms and respond in certain behaviors, and is the grand theory of this study. The aim of this study is to analyze the effect of in-shop emotions and perceived value on the repurchase intention of KKV consumers in Malang City. The method used in this study is quantitative, namely with an associative approach using a Likert scale. The sampling technique applied was nonprobability sampling with the purposive sampling method, involving 96 KKV consumer respondents in Malang City. Then, hypothesis testing will be carried out using SmartPLS software. The results of the study have shown that the in-shop emotions variable has a positive and significant effect on perceived value. Then, the perceived value variable also has a significant effect on repurchase intention. However, perceived value has a positive but not significant effect on repurchase intention